FISHING, PROCESSING, COMMERCIALIZATION AND A PROPOSE TO FISHERY WASTE REUSE OF SURURU Mytella falcata IN THE MUNDAÚ LAGOON, MACEIÓ – AL, BRAZIL - Tamano, Luana Tieko Omena; Lima, Beethoven Brandão Correia de; da Silva, Joseane; Araujo, Daniel de Magalhães (Caminhos de Geografia, 2020)
A diagnosis was made on the fishing, processing, commercialization and generation of residues of the sururu fishery in Mundaú lagoon, Maceió-AL. Thirty nine fishermen were interviewed and also incursions were made for observations. Furthermore, sururus were collected to perform biometry. Residue of the sururu processing was collected to the fabrication of sururu waste meal (SWM), posteriorilly its bromatological composition was analysed. Fishermens of sururus fish 4.56 times week-1 and each fishing excursion lasts 5h26min, yielding 18.61 cans (18.61 to 37.22 kg soft tissue). Besides the sururus, 77.92% also catch fish, shrimp, and other organisms to complement the income. Average selling price was R$ 6.92 per kg of edible and CPUE from 3.42 to 6.85kg edible day-1. The average size and weight are 33.21 mm and 1.62 g, with 782.53 g of waste being generated to produce 1.0 kg of meat. SWM contained 37.00% calcium. It was verified that there is a need to create a management plan capable of reducing environmental impact in the lagoon, implement fishing programs and waste management, as well as improve the structure for the processing of that mollusc. Studies of the use of SWM as a source of calcium in diets are also recommended.